ANALISIS EKSISTENSIALISME FEMINISME DALAM NOVEL LAUT BERCERITA KARYA LEILA SALIKHA CHUDORI - Damyyanus Tarigan; Syifa Hayati (FKIP, Universitas Palangka Raya, 2023)
Culture is a system that lives in society and covers all aspects of human life, from the way of life to the way of thinking. Humans, as creatures who are cultured and knowledgeable, produce literature as a form of expression that expresses reality in writing using elements of beauty. All the treasures of human culture are always based on philosophy or philosophy which is used as the basis and means to achieve true truth. This study aims to analyze the depiction of culture in a novel through the perspective of feminist philosophy and evaluate whether the portrayal of women in social life still occupies an inferior position. This study uses a qualitative approach with a focus on the discourse analysis of the novel, with the aim of describing how women are portrayed in the story and how they are perceived by society. From the results of the research and analysis conducted, it is found that the women in this novel are able to show their freedom, courage, strength, and struggle. However, there are still narratives showing the weakness of women. Nevertheless, the men in the novel recognize that women have an important role in social life and should not be considered as second-class human beings.